2007
DOI: 10.1007/s00421-007-0473-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute moderate hypoxia on anaerobic capacity in endurance-trained runners

Abstract: While there is some controversy whether anaerobic capacity might be improved after altitude training little is known about changes in anaerobic capacity during hypoxic exposure in highly trained athletes. In order to analyze the effects of acute moderate normobaric hypoxia on anaerobic capacity, 18 male competitive triathletes, middle- and long-distance runners VO2max 67.4 +/- 3.8 ml kg min(-1) performed 2 supra-VO2max treadmill runs with the same speed, one in normoxia and one after 4 h exposure to normobaric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…Attention has recently shifted toward IHT in the form of sprint training (Faiss et al, 2013b , 2015 ; Galvin et al, 2013 ; Puype et al, 2013 ), because maximal power (Calbet et al, 2003 ) and anaerobic capacity (Friedmann et al, 2007 ) are well-maintained in hypoxia. This may allow for more explicit systemic and muscular adaptations due to elevated hypoxic and oxidative stress in conjunction with pertinent neuromuscular and neuromechanical loading (Morales-Alamo et al, 2012 ; McGinnis et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Attention has recently shifted toward IHT in the form of sprint training (Faiss et al, 2013b , 2015 ; Galvin et al, 2013 ; Puype et al, 2013 ), because maximal power (Calbet et al, 2003 ) and anaerobic capacity (Friedmann et al, 2007 ) are well-maintained in hypoxia. This may allow for more explicit systemic and muscular adaptations due to elevated hypoxic and oxidative stress in conjunction with pertinent neuromuscular and neuromechanical loading (Morales-Alamo et al, 2012 ; McGinnis et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigated the decrease in aerobic exercise capacity (e.g. HR, SpO 2 , minute ventilation, red blood cell; RBC count, hemoglobin; Hb level, hematocrit; Hct, and VO 2 ) under hypoxic conditions during submaximal exercise and VO 2 max (Lawler et al 1988 ; Calbet et al 2003 ; Friedmann et al 2007 ; Bhaumik et al 2008 ). However, very few studies conducted the effect of acute hypoxia on cardiac function.…”
Section: Introductionmentioning
confidence: 99%
“…However, results have been inconsistent regarding stroke volume (SV), end-systolic volume (ESV), end-diastolic volume (EDV), ejection fraction (EF), systemic vascular resistance (SVR), and CO (Thomson et al 2006 ; Hsu et al 2006 ; Hainsworth and Drinkhill 2007 ; Yan et al 2007 ; Fukuda et al 2010 ). These inconsistencies might have resulted from differences in the study design, extent of hypoxia, exercise type, intensity, and duration (Thomson et al 2006 ; Lawler et al 1988 ; Sunoo et al 1997 ; Morton and Cable 2005 ; Hinckson et al 2006 ; Friedmann et al 2007 ; Adamos et al 2008 ; Elstad et al 2009 ). Therefore, variations in metabolic parameters and cardiac function, and decrease in aerobic exercise capacity under hypoxic conditions have not been explained clearly.…”
Section: Introductionmentioning
confidence: 99%
“…According to this method, the MAOD represents the difference between the predicted oxygen demand and the accumulated oxygen uptake measured during a supramaximal exhaustive test. Previous studies have reported that the MAOD is sensitive in responding to anaerobic training ( 7 ), does not change during acute exposure to hypoxia ( 8 ), and is significantly correlated with muscle phosphocreatine and lactate concentrations ( 3 ). Although these findings suggest that the MAOD might be a valid physiological measurement of anaerobic metabolism, it does not provide separate estimates of the contributions made by alactic (AL MET ) and lactic (LA MET ) metabolism.…”
Section: Introductionmentioning
confidence: 99%